Introduction of chemical engineering - Badger ([S.l.] : McGraw-Hill, 2001)
This book has been written as beginning engineering text, aimed at students who come to the unit operations for the first time. An attempt has been made to introduce such concepts and cite such references as will make the transition to current research work a reasonable step for the student who wishes to go further in any one field.
Keywords: chemical engineering